Highly Flexible Tribovoltaic Nanogenerator Based-on P-N Junction Interface: Comparative Study on Output Dependency Dominated by Photovoltaic Effect in Freestanding-Mode - Sriphan, Saichon; Worathat, Supakarn; Pharino, Utchawadee; Chanlek, Narong; Pakawanit, Phakkhananan; Choodam, Kanokwan; Kanjanaboos, Pongsakorn; Maluangnont, Tosapol; Vittayakorn, Naratip (My University, 2023)
The emergence of tribovoltaic nanogenerators (TVNGs) paves the way for developing a new kind of semiconductor-based energy harvester that overcomes the restriction of low output current in a conventional approach. The traditional TVNG generally depends on the frictional pair between two rigid semiconductors (or metal-semiconductor), limiting the practicability of flexible and portable electronics. Recent developments require the fundamental understanding of charge generation in diverse operating modes and structures. Here, a flexible TVNG based on the p-Cu2O/n-g-C3N4 interface is presented. Operating in a freestanding mode, the proposed TVNG can generate a stable signal in any optical conditions including UV illumination, dark, and ambient. Under UV illumination, the electrical outputs of the TVNG reach 0.43 V and 2.1 µA cm−2, which are significantly larger than those obtained from dark and ambient conditions. The results demonstrate the coupling effect of three phenomena: tribovoltaic, photovoltaic, and triboelectric effects, and the unique mechanism to the observed signal is proposed. Additionally, the TVNG shows the practical feasibility of energy harvesting with capacitor charging and charge-boosting circuits. This study showcases the unique concept with potential for developing a novel flexible nanogenerator in many aspects, including material, structure, and fundamental mechanism.
Keywords: energy harvesting; freestanding triboelectric-layer mode; p-n junctions; photovoltaic effect; tribovoltaic effect